2017
DOI: 10.1038/srep46369
|View full text |Cite
|
Sign up to set email alerts
|

Loop diuretics affect skeletal myoblast differentiation and exercise-induced muscle hypertrophy

Abstract: Muscle wasting or sarcopenia contributes to morbidity and mortality in patients with cancer, renal failure, or heart failure, and in elderly individuals. Na+-K+-2Cl− cotransporter 1 (NKCC1) is highly expressed in mammalian skeletal muscle, where it contributes to the generation of membrane ion currents and potential. However, the physiologic function of NKCC1 in myogenesis is unclear. We investigated this issue using the NKCC1 inhibitors bumetanide and furosemide, which are commonly used loop diuretics. NKCC1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 32 publications
2
48
0
Order By: Relevance
“…Another member of NKCC family, NKCC2, is a major target of loop diuretics in the kidney. The results of these study could suggest that loop diuretics are involved in the loss of skeletal muscle mass and development of sarcopenia . Therefore, sarcopenia in patients with liver cirrhosis might be attributable to treatment with loop diuretics, and the findings of these basic studies, together with the results of our clinical study, could support this hypothesis.…”
Section: Discussionsupporting
confidence: 65%
“…Another member of NKCC family, NKCC2, is a major target of loop diuretics in the kidney. The results of these study could suggest that loop diuretics are involved in the loss of skeletal muscle mass and development of sarcopenia . Therefore, sarcopenia in patients with liver cirrhosis might be attributable to treatment with loop diuretics, and the findings of these basic studies, together with the results of our clinical study, could support this hypothesis.…”
Section: Discussionsupporting
confidence: 65%
“…2D ). The calculated fusion index 8 , which represents the percentage of multinucleated MHC-positive myotubes, was also lower in the WNK1-silenced group, suggesting that the myogenic fusion of myoblasts into myotubes was impaired by WNK1 silencing (Fig. 2E ).…”
Section: Resultsmentioning
confidence: 94%
“…To determine whether WNK1 modulates muscle cell hypertrophy or myogenic differentiation, we measured myotube diameter and the myoblast fusion index 8 after small interfering RNA (siRNA)-mediated silencing of WNK1, SPAK, or OSR1 (Fig. 2A ) using immunofluorescence for MHC in differentiated C2C12 myotubes 4 days after switching the culture medium to DM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandai et al have reported that loop diuretics suppressed skeletal muscle differentiation by blocking Na + -K + -2Cl - cotransporter 1 (NKCC1), which was highly expressed in skeletal muscle by using murine skeletal muscle cells in vitro and in vivo . Thus, NKCC1 was presumed to play an essential role in myogenesis [ 22 ], and it is possible that use of loop diuretics in patients with CKD may elevate the risk of sarcopenia. To date, our study is the first to our knowledge to demonstrate the effect of loop diuretics on risk of developing sarcopenia in a population-based sample.…”
Section: Discussionmentioning
confidence: 99%